Brincante Body: : the travesti presence in the performances of the Reisado quilombos1 - Oliveira Junior, Ribamar José de (Revista Brasileira de Estudos da Presença, 2022)
This article analyzes the performance of the Reisado quilombos from the travesti presence in the popular culture of Juazeiro do Norte, Cariri region, in the countryside of Ceará. In order to reflect on the performance and its animated forms, we consider one of the passages from the cartography that flows through sexual and gender dissidences in Ceará’s Reisados, in which we follow the quilombo of the Sagrada Família group between the performance of gender and the animation of the game. Using the route of one of the first travesti Maestras, we point to the encantravar of the brincante body as a way to praise the travesti body, in the spirals of time played.